2006
DOI: 10.1093/ptj/86.3.355
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High-Grade and Low-Grade Mobilization Techniques in the Management of Adhesive Capsulitis of the Shoulder: Randomized Controlled Trial

Abstract: Background and Purpose. In many physical therapy programs for subjects with adhesive capsulitis of the shoulder, mobilization techniques are an important part of the intervention. The purpose of this study was to compare the effectiveness of high-grade mobilization techniques (HGMT) with that of low-grade mobilization techniques (LGMT) in subjects with adhesive capsulitis of the shoulder. Subjects. One hundred subjects with unilateral adhesive capsulitis lasting 3 months or more and a ≥50% decrease in passive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(131 citation statements)
references
References 29 publications
4
115
0
12
Order By: Relevance
“…Relevant settings (aims and analysis [references]) for SDQ are as follows: General population, primary care (development of the SDQ‐UK [80]) Primary care (development, responsiveness [81]) Primary care (revision, responsiveness [82]) Shoulder instruments (comparative review [83, 84]) Shoulder pain (reliability, validity [85, 86]) Adhesive capsulitis (responsiveness [87, 88]) Rotator cuff (responsiveness [89]) Chronic shoulder pain (responsiveness [90]) …”
Section: Shoulder Disability Questionnaire (Sdq)mentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant settings (aims and analysis [references]) for SDQ are as follows: General population, primary care (development of the SDQ‐UK [80]) Primary care (development, responsiveness [81]) Primary care (revision, responsiveness [82]) Shoulder instruments (comparative review [83, 84]) Shoulder pain (reliability, validity [85, 86]) Adhesive capsulitis (responsiveness [87, 88]) Rotator cuff (responsiveness [89]) Chronic shoulder pain (responsiveness [90]) …”
Section: Shoulder Disability Questionnaire (Sdq)mentioning
confidence: 99%
“…Effect sizes (ES) and standardized response means (SRMs) of the SDQ are as follows: Adhesive capsulitis: mobilization: ES 5.43 and 2.81, SRM 3.88 and 3.40 (ref 87 Rotator cuff tendinitis: steroids, transcutaneous electrical nerve stimulation: ES 5.19 and 5.43, SRM 5.83 and 4.08 (ref 89…”
Section: Shoulder Disability Questionnaire (Sdq)mentioning
confidence: 99%
“…Although there is little evidence to support the use of a wide array of physiotherapy methods as primary or initial treatment for adhesive capsulitis (4–9), there are strong theoretical reasons to suggest that manual techniques and directed exercise may be of value if applied at the appropriate time and/or in combination with other interventions. For example, a recent trial reported small treatment benefits of high‐grade versus low‐grade mobilization techniques in patients with adhesive capsulitis (10). Participants in the trial had a median duration of symptoms of 8 months and the majority had received prior therapy including steroid injections and physical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to maintain the elbow near the side of the trunk and ensure that no pain is experienced during the procedure. Adjust the grade and direction of the glide as needed to achieve pain-free function [10,11]. Three sets of 10 repetitions were applied, with a rest interval of 30 s between each set.…”
Section: Treatment Proceduresmentioning
confidence: 99%